The necropolises of Azerbaijan during the Bronze and Iron Ages in the Lenkoran and the Lerik areas (NABIALLA Project, Azerbaijan): Preliminary report of the 2012–2013 campaigns. (22nd February 2016) - Casanova, Michèle; Lorre, Christine; Alekberov, Abuzar; Fahimi, Hamid; Sauvage, Martin; Haze, Mathias; Vella, Marc-Antoine
Abstract: The NABIALLA Project is a French-Azerbaijani archaeological joint project which tried to reconcile simultaneously two main axes of concern. The Morgan Project, which includes the re-examination of archaeological material formerly discovered and stored in public collections, either in Azerbaijan or abroad, especially in French National Museum of Archaeology (MAN, Saint-Germain-en-Laye) in comparison with archaeological remains found nowadays. The Lenkoran Project intends to study by means of systematic fieldwork the necropolises of the Lenkoran and Lerik provinces (Republic of Azerbaijan) during the Bronze and Iron Ages. This project should result in the better understanding of the funerary practices in the region. This paper presents a summary report of the 2012–2013 campaigns. The Joint Expedition began to conduct fieldwork (surveys and excavation) in the Lenkoran River Valley in 2012. Fieldwork was first conducted at Kraveladi where several megalithic structures have been located within different areas on the banks of the Lakerçay River. In 2013 work was carried out at Cucu Tuk, where a large tumulus was excavated. It contained a double stone circle with a deposit of three pottery vessels which seem to belong to the Late Bronze Age.